Estrutura da fauna bentônica de rodolitos e sedimentos depositados nos recifes lateríticos na Área de Proteção Ambiental Costa das Algas, Aracruz, ES - Neves, Sabrina Brahim (2015)
Sandstone reefs have an important role in the costal zone sheltering a great diversity of organisms, such as benthic invertebrates and fishes, providing protection and food. They pay services to the ecosystems and they are recognized environments of great productivity, constituting a self-sustainable system. In Espírito Santo these environments have unconsolidated sediment deposited over the reefs, mainly composed of bioclastic material like fragments of shells and seaweed, like the rhodolith. Rhodoliths are free-living calcareous seaweeds that display threedimensional structures. By modifying the environment's physical characteristics, they appease the creation of new microhabitats passable of being inhabited by several organisms. This way, the objective of this study was to characterize the spacial and temporal composition and distribution of the benthic community associated to the rhodolith and in the deposited sediments in the lateritic reeds of Gramuté Beach, Aracruz-ES, embbeded in the Costa das Algas Environmental Protection Area. Uni and multifactor analysis showed significant differences in the benthic fauna components among the substrates (p<0,05). Meio and macrofauna had higher number of taxa associated to the rhodolith than in the sediments. The density of the meiofauna was also superior than the rhodolith. On the other hand, the sediment had a higher quantity of organisms of macrofauna organisms than the rhodolith. Copepoda was the mos abundant taxanomic group of the meiofauna, followed by Nematoda and Polychaeta. For the macrofauna, the Polychaeta, from the Syllidae family mainly, presented the higher density throughout all the study in both substrates, followed by the Crustacea and the Nematada in the sediment, and the Ophiuroidea in the rhodolith. Richness and density of macro and meiofauna presented spacial and temporal differences, although macro and meiofauna behaved in different ways. Multivariate analysis corroborate with the results of the univariate, showing variations between substrates, seasons and beach zones. The presence of the rhodolith in the beach of Gramuté contributes to the increase of the heterogeneity of the ecosystem, that increases the richness of taxas and the abundance of benthos in the environment. The characterization of the benthic community and the description of this dynamic aspects discussed here are of extremely importance to assist in conservative actions.